Notes in Brazilian Vernonieae (Asteraceae): two new combinations and a range expansion - Soares, Gleison; Loeuille, Benoît (Phytotaxa, 2021)
Two new combinations in Brazilian Vernonieae are proposed: Critoniopsis bradeana and Vernonanthura glanduloso-dentata. Additionally, the name Vernonia glanduloso-dentata Hieronymus is lectotypified and the geographical distribution of Mesanthophora rojasii is expanded to the Caatinga phytogeographic domain. Descriptions and taxonomic comments are provided for each species.